Step by Step through Hotbeds of Research for School Students (2009)
The hotbeds of research for school students are spaces to stimulate the love for knowledge in children and young people who have already gone through the first stages of EAFIT Children's University and who want to continue being part of the program. In 2009, 13 of such hotbeds were opened in 10 different topics; and about 150 children and young people came to the campus to visit the laboratories, to talk with professors and to delve into the topics that interested them.